Good Homosexual Behaviour Decrease Prevalence of Sexual Transmitted Dissease - Purwaningsih Purwaningsih; Ika Yuni Widyawati; Mohammad Nur Firdaus (Jurnal Ners, 2008)
Introduction: The homosexual behaviour were become indicators of sexually transmitted diseases’s (STDs) prevalencies. Prevalence of sexually transmitted diseases in homosexual community was very high but until recently study it was conducted sporadically. The objective of this study was to analyze the correlation of homosexual behaviour with prevalence of sexually transmitted diseases (STDs) in Mobile Clinic Community Centre of IGAMA collaborating with Public Health Centre Sumberpucung of Malang Regency. Method:  Analytic design with cross sectional methode was used in this study. The population were all visitors of Mobile Clinic Community Centre of IGAMA collaborating with Public Health Centre Sumberpucung of Malang Regency (353 people). Sample were 40 people who met to the inclusion criteria. The independent variable was homosexual behaviour and the dependent variable was prevalence of sexually transmitted diseases (STDs). Data for homosexual behaviour were collected by using questionnaire and indhept interview with content analyze and data for prevalence of sexually transmitted diseases (STDs) were collected by using laboratorium test for STDs. Result: The research result was presented in the form diagram, table of cross tabulation and analyzed by using Spearman Rho with significance level ρ=0.005. The result showed that there was correlation of homosexual knowledge (ρ=0.001), attitude (ρ=0.000) and  practice (ρ=0.000) with prevalence of STDs. Dsicussion:  It can be concluded that the better knowledge, attitude and practice of homosexual could be decrease prevalence of STDs. Futher studies are recomended to analyze the correlation between homosexual behaviour and prevalence of STDs with Health Believe approach.